Regulasi Penggunaan Artificial Intelligence dalam Perizinan UMKM di Kalimantan Tengah - Kencana, Novanita Puspa; Wardhani, Novea Elysa; Hayati, Mulida (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In the era of globalization and technological advances, artificial intelligence (AI) is the main catalyst for the growth of the UMKM sector. In Central Kalimantan, UMKM have a strategic role in local economic development. However, licensing challenges, especially related to the use of AI technology, require understanding and handling relevant legal issues. The purpose of this study is to determine the legal rules for the use of AI in licensing UMKM in Central Kalimantan and to determine the roles and responsibilities of relevant government agencies in supporting the integration of AI technology in UMKM through licensing regulations. Legal certainty is one of the basic principles in law that emphasizes the importance of clear, definite, and predictable laws. In the context of UMKM licensing regulations, this theory can be used to analyze whether existing laws and regulations provide legal certainty for UMKM actors. The following are the legal rules for the use of AI in licensing UMKM in Central Kalimantan Law Number 20 of 2008 on UMKM: regulates the definition, criteria, and rights of UMKM. Law Number 11 of 2020 on job creation (and derivatives): focus on simplifying licensing, including for UMKM. Government Regulation Number 5 of 2021 on risk-based licensing: regulates the classification of risks for licensing. Government Regulation Number 7 of 2021 concerning the ease, protection and empowerment of Cooperatives and SMEs: regulates the ease and empowerment of SMEs. Governor Regulation Number 3 of 2023 concerning the implementation of Risk-Based Business Licensing. UMKM licensing regulations in Central Kalimantan show efforts to provide convenience to small business actors. And the provision of an integrated OSS system is a form of preventive protection by simplifying licensing procedures.